Platelet Inhibitory Drugs: An In Vivo Method of Evaluation in Patients - Norcott, H C; Goldman, M; Hawker, R J; Rafiqi, E I; Drolc, Z; McCollum, C N (Thrombosis and Haemostasis, 1982)
The measurement of platelet deposition in human thrombi is essential for the evaluation of platelet-inhibitory drugs and prosthetic materials for use in patients. The rate of 111Indiumlabelled platelet accumulation on Dacron arterial grafts was measured in 27 patients randomised to take either aspirin and dipyridamole (ASA + DPM) or placebo. Autologous platelets were labelled and re-injected seven days following surgery and the graft thrombogenidty index calculated as the daily rise in the ratio of emissions from the graft over a reference site.The mean (± SD) thrombogenidty index in 12 patients undergoing femoro-popliteal bypass was 0.25 ± 0.09 on placebo and 0.16 ± 0.07 on ASA + DPM started pre-operatively (p Ã0.05). Post-operative ASA + DPM therapy started two days following platelet labelling in 15 patients with aorto-femoral grafts also significantly reduce thrombogenidty to 0.12 ± 0.05 compared with 0.25 ± 0.08 on placebo (p Ã0.01). In the latter patients the ratio of emissions from the graft over reference fell significantly on starting ASA + DPM, suggesting a net loss of platelets from the graft. These results indicate that the rate of in vivo platelet accumulation on Dacron grafts can be quantitated and that ASA + DPM reduced this rate in man.
Keywords: Dacron arterial grafts; Thrombosis - Blood platelets; Platelet metabolism; Arterial occlusive disease; Antiplatelet drugs